1978
DOI: 10.1113/jphysiol.1978.sp012393
|View full text |Cite
|
Sign up to set email alerts
|

Non‐parallel enzyme secretion from rat pancreas: in vivo studies.

Abstract: SUMMARYThe secretion of amylase, lipase and chymotrypsinogen was measured in the pancreatic juice of anaesthetized rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
2

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 26 publications
7
23
2
Order By: Relevance
“…This is associated with a modulatory effect of CCK on biosynthesis, acting preferentially on serine proteases (Renaud et al 1986, Pradel et al 1993, Lloste et al 1994, de Dios et al 1997b. In agreement with previous reports (Dagorn 1978, Grendell et al 1984, our results also show a non-parallel secretion of enzymes in response to short-term CCK stimulation. Under these conditions, differential release of a previously synthesized product may be taking place.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is associated with a modulatory effect of CCK on biosynthesis, acting preferentially on serine proteases (Renaud et al 1986, Pradel et al 1993, Lloste et al 1994, de Dios et al 1997b. In agreement with previous reports (Dagorn 1978, Grendell et al 1984, our results also show a non-parallel secretion of enzymes in response to short-term CCK stimulation. Under these conditions, differential release of a previously synthesized product may be taking place.…”
Section: Discussionsupporting
confidence: 82%
“…Among other effects, CCK regulates the exocrine pancreatic function, and its major action on acinar cells is to stimulate digestive enzyme secretion (Williams & Yule 1993). Under some conditions (Dagorn 1978, Grendell et al 1984, de Dios et al 1997b, the proportion of different enzymes is 'non-parallel'. A selective exocytosis of zymogen granules with different enzyme content has been suggested (Adelson & Miller 1989), however, the mechanism for this phenomenon is still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Control experiments have shown that albumin did not impair the specific activity of chymotrypsinogen after completion of the activation. (Dagorn, 1978 same time. However, the intensity of the stimulation was not the same for the three enzymes.…”
Section: Enzymatic Assaysmentioning
confidence: 71%
“…It was concluded that the non-parallelism between enzyme secretions can occur in the rat upon pancreozyminic or cholinergic stimulation in vitro as well as in vivo (Dagorn, 1978) provided basal protein output is low enough. This is not the case when the tissular integrity of the pancreas is lost, such as in experiments on lobules.…”
Section: Discussionmentioning
confidence: 99%
“…The converse is true for a protein-rich diet (Ben Abdeljilil and Desnuelle, 1964) and the same phenomenon has been described for the lipase-colipase system (Bazin et al, 1978). Such modifications of pancreatic content are now thought to be induced by changes in the biosynthetic rate of individual enzymes rather than by non-parallel secretion (Palade, 1975;Dagorn, 1978) or differential enzyme catabolism (Kramer and Poort, 1972). Changes in the individual rates of enzyme biosynthesis have been shown to occur in the developing embryonic pancreas (Kemp et al, 1972) and also after 30 days (Reboud et al, 1966) and more recently after 5 days of dietary adaptation in the adult rat (Poort and Poort, 1980).…”
Section: Enzymes and Hormones Synthesismentioning
confidence: 99%